Sequestration and potential release of PFAS from spent engineered sorbents - Kah, Melanie; Oliver, Danielle; Kookana, Rai (The Science of the total environment, 2021)
Per- and poly-fluoroalkyl substances (PFAS) have contaminated land and water at numerous sites worldwide that now require remediation. The most common approach for treating contaminated water currently relies on removal of PFAS by sorption. The spent sorbents loaded with PFAS can potentially be disposed of at landfills, provided the sorbed contaminants remain sequestered and certain risk criteria are met. Hence, it is essential that remediation sorbents (i) rapidly adsorb a large variety of PFAS under varying water chemistry conditions, and (ii) do not release the adsorbed PFAS in due course. This review aims at establishing the current state of knowledge about the potential release of PFAS that may occur during and after treatment. The scientific literature currently provides data for a very restricted range of long-chain PFAS. Our knowledge of the dynamics of PFAS adsorption processes on engineered sorbents is limited, and even less is known about their desorption processes. The sorption of PFAS can be strongly affected by changes in the solution pH, ionic strength and dissolved organic matter content, and the process is also subject to complex competition mechanisms in the presence of other PFAS as well as organic contaminants and inorganic salts. Several studies suggest that changes in one or several of these factors may trigger the release of PFAS from engineered sorbents. This phenomenon is more likely to occur for PFAS with shorter carbon chain lengths (<C8), at high pH and in the presence of other PFAS or other anionic sorbates. The release of PFAS from spent sorbent materials, stored or deposited under conditions that vary over time, is highly undesirable, as they can potentially become a secondary source of PFAS in the environment. Our analysis identifies a number of knowledge-gaps that should be urgently addressed in order to design sustainable remediation solutions, including an improved management of spent sorbent materials. [Display omitted] •Remediation of per- and poly-fluoroalkyl substances (PFAS) often relies on sorption.•Very limited data is available on the potential release of PFAS from spent sorbents.•Changes in pH, ionic strength and dissolved organic matter content impact sorption.•PFAS release can be induced by other PFAS or other anionic competitors.•An improved management of spent sorbents is needed.